2017
DOI: 10.1021/acs.joc.6b02711
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Catalyzed Carbonylative Coupling for Synthesis of Arylketones and Arylesters Using Chloroform as the Carbon Monoxide Source

Abstract: We describe a modular, palladium catalyzed synthesis of aryl(hetero)aryl benzophenones and aryl benzoates from aryl(hetero)aryl halides using CHCl as the carbonyl source in the presence of KOH. The reaction occurs in tandem through an initial carbonylation to generate an aroyl halide, which undergoes coupling with arylboronic acids, bornonates, and phenols. Direct carbonylative coupling of indoles at the third position has also been accomplished under slightly modified reaction conditions by in situ activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…Furthermore, we performed a comparison of the catalytic activity of the synthesized palladium(II) complexes with the state‐of‐the‐art catalysts . The results showed that complex 2 has better catalytic activity than other catalysts in terms of yield, catalyst loading, reactions time, turnover number (TON), turnover frequency (TOF), and reusability as shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we performed a comparison of the catalytic activity of the synthesized palladium(II) complexes with the state‐of‐the‐art catalysts . The results showed that complex 2 has better catalytic activity than other catalysts in terms of yield, catalyst loading, reactions time, turnover number (TON), turnover frequency (TOF), and reusability as shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the use of chloroform as a CO surrogate has grabbed the attention of organic chemists for the synthesis of a variety of targeted organic molecules . The in situ ‐generated CO from CHCl 3 and a base has been used in various organic reactions such as carboxylation, carbonylative coupling, aminocarbonylations, Heck‐type domino cyclization, and carbonylative Sonogashira coupling . Recently, one of us has elegantly demonstrated the application of this methodology (chloroform as CO surrogates) in aminocarbonylation of 7‐azaindole and imidazopyridines, leading to the synthesis of biologically important aminocarbonyl‐functionalized 7‐azaindole and 2‐amidoimidazo[1,2‐ a ]pyridines .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] To the best of our knowledge, the carbonylative Suzuki-Miyaura cross-coupling using CO surrogates has only been performed under homogeneous catalytic protocols. Moreover, the carbonylative Suzuki-Miyaura cross-coupling under CO surrogacy has been performed mostly in hydrocarbon solvents [5,6,[8][9][10] (anisole and toluene) and N,N-dimethylformamide. Moreover, the carbonylative Suzuki-Miyaura cross-coupling under CO surrogacy has been performed mostly in hydrocarbon solvents [5,6,[8][9][10] (anisole and toluene) and N,N-dimethylformamide.…”
Section: Introductionmentioning
confidence: 99%
“…In these protocols, high pressure of CO gas is essentially required not only to get the good yield of desired ketones but also to reduce the formation of byproducts. A search in the literature revealed that several compounds like formic acid, formates, chloroform, aldehydes and other CO surrogates have been used as CO source. In addition, few metal carbonyls were also used as CO source .…”
Section: Introductionmentioning
confidence: 99%